Utilization of Rice Straw and Wheat Straw for Production of Lactic Acid - Kaur, Tavinder (My University, 2017)
Present research work was aimed at utilization of lignocellulosic biomass such as rice straw and wheat straw for production of lactic acid. Rice straw and wheat straw were collected from nearby villages of Patiala. Since lignocellulosic materials exhibit strong recalcitrance to enzymes, a suitable prior pretreatment was done to facilitate access of enzymes to the plant polysaccharides. Acid and alkali hydrolysis of rice straw and wheat straw biomass was done to obtain hydrolysates followed by detoxification using calcium hydroxide to neutralize the effect of inhibitors. Fermentation using different strains of bacteria i.e. DGB, NA9, DGN1 and DGN2 was carried out in enrichment broth containing 10 g/L xylose and 5 g/L yeast extract (pH 7) and at different temperatures (25 ̊C, 37 ̊C, 45 ̊C and 50 ̊C). The maximum growth of DGN1 was observed at 50 ̊C with 58.85 g/L of lactic acid production and overall productivity of 1.23g/L/h followed by DGB with lactic acid concentration of 56.65 g/L and overall productivity of 1.18 g/L/h. Using glucose+xylose as substrate in Bushnell Haas minimal medium, maximum lactic acid titer of 18.08 g/L was obtained using Bacillus licheniformis (DGB) with overall productivity of 0.38 g/L/h at optimum temperature of 50 ̊C. Bacillus licheniformis (DGB) was used to produce lactic acid by exploiting sugars from hydrolysates of rice straw and wheat straw obtained after pretreatment and detoxification at 50 ̊C with agitation at 120 rpm, after 72 hr incubation. The maximum lactic acid titer of 96.21g/L was reported using concentrated sulphuric acid pretreated and detoxified rice straw hydrolysates with an overall productivity of 1.59 g/L/h, whereas in case of wheat straw maximum lactic acid titer of 114.22 g/L was obtained in alkali pretreated hydrolysates with an overall productivity of 1.33 g/L/h. Results showed that Bacillus licheniformis (DGB) was an efficient strain for lactic acid production from pretreated lignocellulosic biomass. Utilization of rice straw pretreated with concentrated sulphuric acid and detoxification and wheat straw pretreated dilute alkali alone is an efficient method for higher lactic acid production.
Master of Science -Biotechnology
Keywords: Lactic Acid; Wheat Straw; Rice Straw; Thermotolerant Bacteria